The Influence of Price Earning Ratio and Earning Per Share on Stock Returns in the Transportation and Logistics Sub-Sector Listed on the IDX - Aliyah, Dini Rahma; Bangun, Mudtiani Hakim Br; Lubis, Salsabila Azzahro; Sitorus, Atikah Zuhra; Hafsa, Alma; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
This study investigates the impact of two financial parameters - Price Earning Ratio (PER) and Earnings per Share (EPS) - on stock returns of transportation and logistics companies listed on the IDX. Both metrics are fundamental analysis tools that help investors evaluate the potential and value of a company's stock. The selection of the transportation and logistics sector is based on its significance in driving the national economy and distribution, although this sector is also vulnerable to external pressures that can impact its financial performance. A quantitative approach through multiple linear regression is applied in this research, using historical data in the form of financial reports and stock price movements from transportation and logistics issuers on the IDX. In the research model, PER and EPS act as independent variables, while stock returns are the dependent variables. The analysis reveals that both parameters have a significant impact on stock returns, with EPS showing a more dominant positive influence than PER. This suggests that earnings per share plays a greater role in determining the level of stock returns in this sector. The results of this study provide valuable insights for capital market players in making investment decisions based on financial indicators. This study also contributes to the development of knowledge related to fundamental factors that influence stock returns, while providing references for investment strategies in the transportation and logistics sector of the IDX.